(untitled) (Global Journal of Management and Business Research, 2018)
RMG (Ready-made garments) earns most of the foreign currency among all the sectors in Bangladesh. Bangladesh has secured the second position regarding exporting RMG next to China. In the last 40 years, the RMG sector of Bangladesh has experienced a dramatic emergence as one of the top sourcing hubs for apparel buying throughout the world. Most of the world famous clothing brands buy apparels from Bangladesh and sell them as their products. The main reason for the popularity of Bangladesh as a sourcing hub in RMG sector is lower price compared to other garment making countries. Though Bangladesh is earning a considerable amount of foreign currency and has all the resources to create own international brands, in the history of forty years of its RMG sector, it could not establish any renowned international clothing brands. But the time has come to initiate Bangladeshi own global brands as the global market economy is changing gradually as well as the competition is also increasing. This paper along with defining different aspects of branding shows the possible strategies that can be proved instrumental in creating own global clothing brands of Bangladesh.